Research and implementation of“optical access sandwich”solution in broadband access network - Jun DU (Dianxin kexue)
With the continuous promoting of“Broadband-China”evolution，“Faster internet with cheaper tariff”in broadband field has become the important support of“internet+”.The optical access-sandwich solution was proposed based on the gradual evolution from 2G to 3G，which means reusing traditional incoming-line on the live network，distributed by replacing traditional GYTA fiber with butterfly-flexible optical cable and providing convergent DP in FTTH and FTTB. The asset-light and high-bandwidth on fixed access network can be achieved effectively with the large-scale deployment on the solution. In the environment of next generation internet，the advantage on optical access-sandwich，including advanced-technology and effective-cost，was analyzed. Meanwhile，the key point，which is reflected in the modernized telecom infrastructure in internet+，was summarized accordingly. The proposal，which included acceleration on optical-internet modernization and the asset-light & high-bandwidth on network，was put forward.